Accession to the European Union: advantage or disadvantage for Czech companies? - Litva, Dušan (Business, Management and Economics Engineering, 2016)
In this paper has been studied effects of accession to the EU on Czech companies which were selected and grouped according to 5 parameters: region, legal form, operation area, business sector and size of the company defined by number of employees. Questionnaire containing 14 questions have replied in total 146 respondents. It is possible to conclude that accession to the EU brought more advantages to big global joint- stock companies than to small regional companies which were mostly negative and claimed worsening of business results due to European integration. Most of the 146 respondents asked via questionnaire containing 14 questions did not agree with acceptance of Euro, while those who agreed had been estimated 2020 as ideal year to access Eurozone. Companies in quaternary sector were mostly positive on the opposite to the companies in tertiary sector which were negative. Companies in Prague and Central Bohemia were much more positive towards EU benefits than in rest of the Czech Republic regions.